Efflux Pumps and These Inhibitors - Khac Minh, Thai; Thanh Dao, Tran; Thien Vy, Phan; Tran Giang Son, Do; Tung, Hoang; Hoang Minh, Nguyen; Minh Tri, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 35 No 2DO - 10.25073/2588-1132/vnumps.4188, 2019)
In this era of multi-drug resistance, efflux pump is one of the major problems which is increasingly concerned by scientists. The structure and mechanism activity of the efflux pumps on both bacteria and eurakyotes that are gradually being clarified. Since then, efflux pump inhibitors have also been studied and initially applied in clinic, that makes an important contribution to preventing the outbreak of multi-resistant infections and cancers. Efflux pump inhibitors are often small synthetic molecules or plant metabolites that show great promise in inhibiting multi- resistant in both bacteria and cancerous cells. Keywords Efflux pump, EPI, bacteria, cancer, MRD. References [1] Ministry of pulic health, Decision on Guidelines for the Management of Community-Based Pneumonia in children 2014 (in Vietnamese). [2] UNICEF Viet Nam, The top two fatal diseases for children in the Asia-Pacific region and Viet Nam, 2012 (in Vietnamese). [3] Nguyen Van Quang, Analysis of the cost of treating decompensated cirrhosis due to hepatitis C at Ho Chi Minh Tropical Hospital and Bach Mai Hospital in Ha Noi 2015 University graduation thesis in pharmacy (2017) (in Vietnamese). [4] Duc Anh Dang, Kah Kee Tan, Ki Hwan Kim, Cissy Kartasasmita, et al, Burden of hospitalized childhood community-acquired pneumonia: A retrospective cross-sectional study in Vietnam, Malaysia, Indonesia and the Republic of Korea, Human vaccin Immunother 14 (1) (2018) 95-105. https://doi.org/10.1080/21645515.2017.1375073. [5] Philip Ayieko, Ulla Griffiths, Angela Oloo Akumu, Mike English, The economic burden of inpatient paediatric care in Kenya: household and provider costs for Treatment of pneumonia, malaria and meningitis.; Cost Effectiveness and Resource Allocation 7(3) (2009) 1-13. https://doi.org/10.1186/1478-7547-7-3. [6] Nguyen Ngoc Tu, Analyze the direct cost of treating community-acquired pneumonia at Thai Nguyen tuberculosis and lung disease year 2015, Master's thesis in pharmacy (2017) (in Vietnamese). [7] Bui Thi Quyen, Analyze the cost of treating community-acquired pneumonia at the children's hospital in Nam Dinh province 2015, Grade 1 specialized pharmacist thesis (2016) (in Vietnamese). [8] Hamidah Hussain, Hugh Waters, Aamir J Khan, Saad B Omer, et al, Economic analysis of childhood pneumonia in Northern Pakistan, Heatlh policy plan 23(6) (2008) 438-444. https://doi.org/10.1093/heapol/czn033.